Analysis of fulfillment of domestic clean water needs of Muara Baru village, Air Kumbang subdistrict, Banyuasin regency using the rainwater harvesting (RWH) method - Sabrina, Balqis; Juliana, Imroatul Chalimah (Edelweiss Applied Science and Technology, 2025)
Rainwater Harvesting (RWH) is a method of collecting rainwater for alternative sources of clean water. The purpose of this study is to carry out RWH planning, including determining strategies and conducting feasibility analysis based on the quality and quantity of rainwater in Muara Baru Village, which is an area with critical water catchment conditions and is not yet served by a clean water pipeline network. The primary data collected included three types of houses, the number of different residents, and sampling the quality of rainwater and groundwater at the site. The selected water catchment area is the roof surface of the house. In terms of quantity, the potential supply of rainwater meets the needs for non-drinking water use. In terms of quality, rainwater samples have not met the quality standards for clean water based on Permenkes 32/2017. The rainwater collected will go through a disinfection and filtration process so that it meets the quality standards of clean water, and then it will be stored in the ground tank and roof tank to be distributed to each house. Thus, the planned RWH is able to provide an alternative source of clean water for the community in the Muara Baru Village area.